Pengaruh Plastimen-VZ Pada Beton Dengan Agregat Pasir Pantai Sejarah Kabupaten Batu Bara - Irwansyah, Muhammad; Z, Fynnisa; Septiriawan, Gilang; Maharani, Dwi; Damanik, Ficha Zuanda (Universitas Teuku Umar, 2023)
The use of concrete in construction continues to increase, so innovation in making concrete continues to grow. One of the innovations used in this study is to use additives to analyze the effect of concrete compressive strength on the use of historical beach sand and chemical additives (Plastimen-VZ) as concrete mixes using Mix Design SNI 2834-2000. Testing of the compressive strength of concrete was carried out at 3 and 7 days of age with a reference to normal concrete control of 24.90 MPa or equivalent to K-300 and the number of samples consisted of 18 samples with the added chemical Plastiment-VZ (Sika) 0%, 0.40 %, 0.80%. The results of the study using historical beach sand and Plastimen-VZ (Sika) meet the specifications for use as a concrete mix with a normal concrete control reference of 24 MPa with a compressive strength value of 24.76 MPa. The results of the compressive strength of concrete with a mixture of beach sand and Plastimen-VZ (Sika) 0.40% aged 3 days obtained an average of 24.99 MPa. The results of the compressive strength of concrete with a mixture of beach sand and Plastimen-VZ (Sika) of 0.80% aged 7 days obtained an average of 25.03 MPa.